International Negotiation in China and India A Comparison of the Emerging Business Giants - Kumar, R. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
Negotiation is an important managerial skill. The ability to negotiate across cultures becomes even more challenging due to differences in institutional practices. This book explores how the institutional environment in India and China shapes their negotiating behaviour.